On the Management of Scientific Research Work in Colleges and Universities of Western Areas - Zhang, Xiaoyun; Li, Dongmei (International Journal for Innovation Education and Research, 2015)
According to the existing condition analysis of academic research management in colleges and universities of the western areas, pointing out there being some existing problems at present, and putting forward to the countermeasures solving these problems. Thinking, as for the colleges and universities of the western areas, on the management of academic research work, are supposed to grasp the complication of it, highlight the local unique features, strengthen the ability of serving local economic, and take an important part in the local economic development.